Non-uniform Segmental Range of Motion of the Thoracic Spine During Maximal Inspiration and Exhalation in Healthy Subjects - Burgos, Jesús; Barrios, Carlos; Mariscal, Gonzalo; Lorente, Alejandro; Lorente, Rafael (Frontiers in Medicine, 2021)
Background and objective: To analyse the range of motion of the thoracic spine by radiographically measuring changes in the sagittal profile of different thoracic segments during maximal inspiration and exhalation. The starting hypothesis was that forced deep breathing requires an active, but non-uniform widening of the lordotic–kyphotic range of motion of the different thoracic segments. Methods: Cross-sectional study. Participants were 40 healthy volunteers aged 21 to 60. Conventional anteroposterior and functional sagittal chest radiographs were performed during maximal inspiration and exhalation. The range of motion of each spinal thoracic functional segment, global T1–T12 motion, and the sagittal displacement of the thoracic column during breathing were measured. Considering the different type of ribs and their attachment the spine and sternum, thoracic segments were grouped in T1-T7, T7-T10, and T10-T12. The displacement of the thoracic spine with respect to the sternum and manubrium was also recorded. Results: The mean difference from inspiration to exhalation in the T1–T12 physiologic kyphosis was 15.9°±4.6°, reflecting the flexibility of the thoracic spine during deep breathing (30.2%). The range of motion was wider in the caudal hemicurve than in the cranial hemicurve, indicating more flexibility of the caudal component of the thoracic kyphosis. A wide range of motion from inspiration to exhalation was found at T7–T10, responsible for 73% of T1–T12 sagittal movement. When the sample was stratified according to age ranges (20-30 yr., 30-45 yr., and 45-60 yr.), none of the measurements for inspiration or exhalation showed statistically significant differences. Only changes at this level showed a positive correlation with changes in the global thoracic kyphosis (r=0.794, p<0.001). Conclusion: The range of motion of the thoracic spine plays a relevant role in respiration dynamics. Maximal inspiration appears to be highly dependent on the angular movements of the T7–T10 segment.